SUMBERDAYA TERIPANG DI PERAIRAN TANJUNG PAI PADAIDO BIAK NUMFOR PAPUA - Yusron, Eddy (UI Scholars Hub, 2004)
Sea Cucumber Resources At Tanjung Pai Waters Padaido Biak Numfor Papua. Observation on sea cucumber diversity was carried out at coastal waters of Pai and Imbeyomi Islands in the Padaido Island Biak Numfor. Sampling was done by using a transect quadrant of 1 m x 1 m. This sampling and observation on its microhabitat were conducted by snorkling. Analyses on the sea cucumber community structure were based on its frequency of occurance, diversity, and density. The results showed that at both locations 10 species of sea cucumber were found where Holothuria edulis, H. atra, and H. nobilis were predominant common and more evenly distributed than the other species.